2015
DOI: 10.1007/s12665-015-4432-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality and hydrochemistry of groundwater used for drinking in Lahore, Pakistan: analysis of source and distributed groundwater

Abstract: More than 7 million people of Lahore city, Pakistan, use groundwater for drinking and other household purposes. The quality of drinking water from source and distribution system was investigated, and the hydrochemical characteristics and formation mechanisms of groundwater were analyzed. Statistical summary showed higher mean values of major descriptors in distributed groundwater samples compared with source groundwater samples. A total of 50 drinking water samples (16 from source, and 34 from distribution sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Table 6 provides a comparison of this condition with other investigations. Studies have indicated that using softened water can increase the cycle of concentration (Abbas et al, 2015), however, this study's freshwater quality is suitable for cooling tower systems, as shown by previous research (Siddique et al, 2021).…”
Section: Reduction Of Cooling Water Consumption At Syntan Plantmentioning
confidence: 60%
“…Table 6 provides a comparison of this condition with other investigations. Studies have indicated that using softened water can increase the cycle of concentration (Abbas et al, 2015), however, this study's freshwater quality is suitable for cooling tower systems, as shown by previous research (Siddique et al, 2021).…”
Section: Reduction Of Cooling Water Consumption At Syntan Plantmentioning
confidence: 60%
“…The observed mean alkalinity value indicates presence of large quantities of alkaline substances in raw and filtered water, which can help buffer against sudden pH changes. High alkalinity is disagreeable because it causes deposits of carbonate salts and encrustations in distribution systems causing corrosion and effect the durability of the system (Abbas et al, 2015). Significant variability in alkalinity levels within the study area suggesting alkalinity changes along different location depending upon the dissolution of bicarbonates minerals and the underlying geology.…”
Section: Alkalinitymentioning
confidence: 92%
“…Bicarbonates in combination with polyvalent ions such as calcium and magnesium cations cause temporary hardness which can result in scale formation in the distribution pipe systems of water (Abbas et al, 2015) (Ponsadailakshmi et al, 2018). Due the presence of bicarbonates water of filtration plants is highly alkaline and may cause hardness and corrosion in plumbing system.…”
Section: Alkalinitymentioning
confidence: 99%
“…Threats to water quality include operational at water sources while water mains and bacterial pollution, harmful metals such as arsenic, sewer. Abbas et al (2015) [29] assessed the quality iron, cadmium, and nickel, pesticides, and in of drinking water at the source and throughout the certain locations nitrates and fluorides within distribu tion system, and they examined the Pakistan [17]. Iron is a major element required by hydrochemical properties and formation processes our body.…”
Section: Total Hardness and Alkalinitymentioning
confidence: 99%